Successful Surgical Treatment of a Brain Stem Hydatid Cyst in a Child - Rahaf Alok; Jaber Mahmoud (Case Reports in Surgery)
Hydatid disease is a parasitic infestation, which is endemic in the Mediterranean region. It is often located in the liver and the lungs, whereas brain stem hydatid cysts are extremely rare. We report a case of a five-year-old female who presented with hemiparesis, and after investigations, she was diagnosed with a hydatid cyst in the pons. She also had cysts in her liver and kidney. The cerebral cyst was completely removed without rupture, using gentle water-jet dissection (Dowling’s technique). She was feeling well after 4-month follow-up. We emphasize the importance of keeping hydatid cysts in the differential diagnosis of pediatric infratentorial cystic lesions.